Analysis of the Performance of 11 Formulae for Fetal Weight Estimation in Preterm Fetuses with Abnormal Doppler Velocimetry – A Retrospective Multicenter Study - de Lima, Alessandra Martins Heringer; de Carvalho, Paulo Roberto Nassar; Junior, Saint Clair Gomes; Carioca, Ana Carolina Costa; Lopes, José Maria de Andrade (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To assess 11 formulae commonly used to estimate fetal weight in a population of premature fetuses who had abnormal Doppler velocimetry due to early-onset placental insufficiency. The performance of each formula was evaluated in subgroups of fetuses with expected growth and intrauterine growth restriction.Methods Data were collected from fetuses and mothers who delivered at three Brazilian hospitals between November 2002 and December 2013. We used the following formulae: Campbell; Hadlock I, II, III, IV and V; Shepard; Warsof; Weiner I and II; and Woo III.Results We analyzed 194 fetuses. Of these, 116 (59.8%) were considered appropriate for gestational age (AGA), and 103 (53.1%) were male. The amniotic fluid volume was reduced in 87 (44.8%) fetuses, and the umbilical artery Doppler revealed absence or inversion of diastolic flow in 122 (62.9%) cases, and the analysis of the ductus venosus revealed abnormal flow in 60 (34.8%) fetuses. The Hadlock formulae using three or four fetal biometric parameters had low absolute percentage error in the estimated fetal weight among preterm fetuses with abnormal Doppler studies who were born within 5 days of the ultrasound evaluation. The results were not influenced by the clinical and ultrasound parameters often found in early-onset placental insufficiency.Conclusion In this study, the formulae with the best performance for fetal weight estimation in the analyzed population were Hadlock I and IV, which use four and three fetal biometric parameters respectively to estimate the weight of preterm fetuses with abnormal Doppler studies.
Keywords: fetal weight; birth weight; premature birth; ultrasound; prenatal ultrasound; doppler ultrasound; fetal growth retardation; placental insufficiency